Interleukin (IL)‐22 receptor 1 is over‐expressed in primary Sjogren's syndrome and Sjögren‐associated non‐Hodgkin lymphomas and is regulated by IL‐18. (3rd June 2015) - Ciccia, F.; Guggino, G.; Rizzo, A.; Bombardieri, M.; Raimondo, S.; Carubbi, F.; Cannizzaro, A.; Sireci, G.; Dieli, F.; Campisi, G.; Giacomelli, R.; Cipriani, Paola; et al.
Summary The aim of this study was to elucidate more clearly the role of interleukin (IL)‐18 in modulating the IL‐22 pathway in primary Sjögren's syndrome (pSS) patients and in pSS‐associated lymphomas. Minor salivary glands (MSGs) from patients with pSS and non‐specific chronic sialoadenitis (nSCS), parotid glands biopsies from non‐Hodgkin lymphomas (NHL) developed in pSS patients, were evaluated for IL‐18, IL‐22, IL‐22 receptor 1 (IL‐22R1), IL‐22 binding protein (IL‐22BP) and signal transducer and activator of transcription‐3 (STAT‐3) expression. MSGs IL‐22R1‐expressing cells were characterized by confocal microscopy and flow cytometry in pSS, nSCS and healthy controls . The effect of recombinant IL‐18 and IL‐22 on peripheral blood mononuclear cells (PBMCs) from pSS and nSCS was studied by flow cytometry and reverse transcription–polymerase chain reaction (RT‐PCR). MSGs of pSS and NHL were characterized by an imbalance between IL‐22 and IL‐22BP protein expression, with IL‐18 and IL‐22BP being expressed in a mutually exclusive manner and IL‐18 and IL‐22R1 being correlated directly. Aberrant expression of IL‐22R1, induced by IL‐18, was observed only among tissue and circulating myeloid cells of pSS patients and macrophages of NHL tissues of pSS patients, but not nSCS. IL‐22R1 expression on PBMC of pSS was functional, as its stimulation with recombinant IL‐22 significantly up‐regulated the expression of STAT‐3, IL‐17 and IL‐22. An IL‐18‐dependent aberrant expression of IL‐22R1 on cells of haematopoietic origin seems to be a specific immunological signature of patients with pSS and pSS‐associated lymphomas.